Ensuring Content Representativeness: Perceptions of Senior High School Teachers in Ghana - Asamoah, Daniel; Sundeme, Benjamin; Adusei, Aaron; Ocansey, Moses K. K.; Ntim, William Ntiamoah (International Journal of Educational Technology and Learning, 2019)
For a meaningful classroom assessment to be feasible, teachers must ensure adequate content representativeness when crafting their items. The study sought to find out the perceptions of senior high school teachers on how well they ensure content representativeness in their classroom assessment procedures in Ghana. Underpinned by the theory of validity, the study used the qualitative research approach. The purposive sampling procedure was used to select a sample of 25 participants for the study. The interview guide was used to collect data for the study. The data was analysed manually using the thematic approach. The results of the study revealed that senior high school teachers least ensure content representativeness in their assessment procedures because they fail to develop and use a table of the test specification. In furtherance to this, the study showed that senior high school teachers do not consult measurement experts or curriculum planners to thoroughly judge the items the teachers craft in ensuring content representativeness. It is recommended among others that there should be the need for educating teachers on what table of a test specification is, and how to develop and use it.